Transgenic crops VI - Pua, Eng Chong. (Biotechnology in agriculture and forestry, 2007)
Genetic engineering is a powerful tool for crop improvement. The status of crop biotechnology before 2001 was reviewed in Transgenic Crops I-III, but recent advances in plant cell and molecular biology have prompted the need for new volumes. Following Transgenic Crops IV (2007) on cereals, vegetables, root crops, herbs, and spices, and Transgenic Crops V (2007) on fruits, trees, and beverage crops, this volume, Transgenic Crops VI, contains the following sections: Oils and Fibers, Medicinal Crops, Ornamental Crops, Forages and Grains, Regulatory and Intellectual Property of Genetically Manipulated Plants. It is an invaluable reference for plant breeders, researchers and graduate students in the fields of plant biotechnology, agronomy, horticulture, forestry, genetics, and both plant cell and molecular biology. Oils and Fibers -- Soybean -- Canola -- Sunflower -- Oil Palm -- Peanut -- Cotton -- Flax -- Medicinal Crops -- Ginseng -- OpiumPoppy -- Henbane, Belladonna, Datura and Duboisia -- Taxus -- Ornamental Crops -- Roses -- Carnation -- Chrysanthemum -- Orchids -- Gladiolus -- Forsythia -- Forages and Grains -- Alfalfa -- Clover -- Tall Fescue -- Ryegrasses -- Lupins -- Regulatory and Intellectual Property of GM Plants -- Freedom to Commercialize Transgenic Plant Products: Regulatory and Intellectual Property Issues.